Relationship between neutrophil albumin ratio and SOFA score in sepsis patients at Wahidin Sudirohusodo Hospital - Sofyan, Aulia Istiqamah; Risna Halim ,; Suriani Alimuddin,; Syakib Bakri,; Sudirman Katu,; Andi Alfian Zainuddin, (Acta Biomedica Atenei Parmensis, 2024)
Background and Aim: Sepsis is organ dysfunction due to dysregulation of the body's response to infection. Currently, there are several parameters to predict outcomes in sepsis patients. Recently, neutrophil to albumin ratio (NAR) was developed to predict sepsis severity, but studies are still limited. This study was conducted to determine the relationship between NAR and sepsis severity. Methods: This study was a cross-sectional study at Dr. Wahidin Sudirohusodo Hospital, Makassar. We included sepsis patients aged ≥18 years and blood were taken for laboratory examination. Sepsis was diagnosed if the SOFA score was ≥2 and NAR was the ratio of neutrophil count (%) and albumin (gr/dL) based on laboratory results. Data were analyzed using a logistic regression test and Chi-square test. Results: 60 subjects met the study criteria with 32 female subjects and a mean age of 54.67 ± 14.45 years. This study found that patients with SOFA scores≥8 had a higher mean NAR value, which was 29.09. The logistic regression test results obtained an OR value of 29.9; p = 0.032. In addition, the cut-off value of NAR to predict SOFA score ≥8 was 33.4 with a sensitivity of 94% and specificity of 96%. Conclusions: This study found that there was a significant association between increased NAR with SOFA scores. A higher neutrophil count was proportional to a higher SOFA score, while lower albumin was proportional to a higher SOFA score.